The global learning crisis - Costin, Claudia (Institutional Knowledge at Singapore Management University, 2019)
In September 2015, the UN General Assembly approved the Sustainable Development Goals (SDGs), one of which, the SDG-4, focuses on the educational goal of ensuring free, equitable and quality primary and secondary education that will lead to relevant and effective learning outcomes. This goal, which is to be achieved by 2030, is ambitious. Even today, there are too many children without access to a school, or those who are not learning the basics, or dropping out of school.